2000
DOI: 10.1046/j.1365-3180.2000.00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing foliar activity of glyphosate on Bidens frondosa and Panicum maximum with different adjuvant types

Abstract: The in¯uence of non-ionic (X-77) and organosilicone (L-77) adjuvants and of methylated seed oil (MSO) on the uptake, translocation and ecacy of glyphosate was investigated in Bidens frondosa L. and Panicum maximum Jacq. In addition, the physicochemical properties of adjuvants and adjuvant + glyphosate aqueous solutions were determined. Signi®cantly lower surface tension and contact angle values were obtained with aqueous solutions of L-77 alone and with glyphosate. Over a 48-h time course, it was observed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 22 publications
0
25
0
1
Order By: Relevance
“…Nanoemulsions have been reported to increase the penetration of incorporated drugs distinctly for oral, topical and intravenous administration . The use of vegetable‐oil‐based adjuvant has been shown to improve the penetration of many herbicides, including glyphosate IPA , . There is evidence that organosilicone wetting agents could enhance the absorption of the herbicide primisulforon into plant tissue, with greater weed control .…”
Section: Discussionmentioning
confidence: 99%
“…Nanoemulsions have been reported to increase the penetration of incorporated drugs distinctly for oral, topical and intravenous administration . The use of vegetable‐oil‐based adjuvant has been shown to improve the penetration of many herbicides, including glyphosate IPA , . There is evidence that organosilicone wetting agents could enhance the absorption of the herbicide primisulforon into plant tissue, with greater weed control .…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong correlation between the translocation and the absorption of a herbicide in the plants [14], [16], [43]. In this study, MSO significantly increased absorption and translocation of topramezone for giant foxtail, but it significantly increased only absorption of this herbicide but not translocation for velvetleaf.…”
Section: Resultsmentioning
confidence: 46%
“…Xu et al reported that MSO could decrease the surface tension and contact angle and then increase the wetted areas of droplets on both waxy and hairy leaves [7], [8]. Some reports have shown that MSO enhances the efficacy of several herbicides on certain weed species by increasing the absorption of the herbicides by weeds [9], [10], [11], [12], [13], [14], [15], [16]. Topramezone, a hydroxyphenylpyruvate dioxygenase inhibitor, was commercially introduced in the year of 2006 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Sharma and Singh [50] evaluated the influence of non-ionic (X-77) and organosilicone (L-77) adjuvants and methylated seed oil (MSO) on the uptake, translocation and efficacy of glyphosate in Bidens frondosa L. and Panicum maximum Jacq. In B. frondosa, all three adjuvants significantly increased the uptake and translocation of glyphosate.…”
Section: Influence Of Surfactants On Glyphosate Efficacymentioning
confidence: 99%